Angels and Loners: An Examination of Abstainer Subtypes. Issue 12 (1st December 2016) - Hendrix, Joshua A.
ABSTRACT: Scholars speculate that there may be both prosocial and antisocial modes of abstention; however, few attempts have been made to examine this idea empirically. Using a pooled sample from the National Longitudinal Survey of Youth 1979, group-based trajectory analysis is presented to identify adolescents who abstain from marijuana, vandalism, violence, and theft during their teenage years, and latent class analysis is used to examine within-group heterogeneity among abstainers. A subset of abstainers report weak peer integration, psycho-emotional instability, worse academic performance, and more conflict with their parents. Implications of findings are discussed.